Novel spectrum sharing strategy based on QoS support in cognitive vehicular network - Lei ZHANG; Tao LUO; Wei LIU (Tongxin xuebao)
A two-step spectrum sharing strategy consisting of inter-cell allocation and intra-cell allocation was developed to guarantee the system quality of service(QoS)in the cognitive vehicular network(CVN).Simulation results indicate that the proposed GNBS scheme considering both the fairness and utility can obtain larger transmission rate than Max-min scheme and achieve much better fairness than Max-rate scheme.Considering the difference of spectrum requirements between cognitive cells,GNBS scheme can allocate the spectrum resource dynamically in a weighted fairness manner.Furthermore,the cognitive cooperative spectrum sharing scheme outperforms than the non-cooperative scheme,and it can greatly improve the system utility and fairness between OBU than the non-cooperative schemes.